Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/jvh.12648
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of sofosbuvir‐based regimens plus an NS5A inhibitor for patients with HCV genotype 3 infection and cirrhosis. Results of a multicenter real‐life cohort

Abstract: Patients with HCV genotype 3 (GT3) infection and cirrhosis are currently the most difficult to cure. We report our experience with sofosbuvir+daclatasvir (SOF+DCV) or sofosbuvir/ledipasvir (SOF/LDV), with or without ribavirin (RBV) in clinical practice in this population. This was a multicenter observational study including cirrhotic patients infected by HCV GT3, treated with sofosbuvir plus an NS5A inhibitor (May 2014-October 2015). In total, 208 patients were included: 98 (47%) treatment-experienced, 42 (20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
(36 reference statements)
4
24
1
Order By: Relevance
“…A study from Spain reported an overall SVR12 of 93.8% in genotype 3 patients treated with sofosbuvir and daclatasvir combination therapy . Another study in Asian American patients with CHC and advanced liver disease (genotypes 1, 2, 3 and 6), treated with multiple oral DAA combinations, reported a similar overall SVR .…”
Section: Discussionmentioning
confidence: 89%
“…A study from Spain reported an overall SVR12 of 93.8% in genotype 3 patients treated with sofosbuvir and daclatasvir combination therapy . Another study in Asian American patients with CHC and advanced liver disease (genotypes 1, 2, 3 and 6), treated with multiple oral DAA combinations, reported a similar overall SVR .…”
Section: Discussionmentioning
confidence: 89%
“…DAA therapy outcomes had variability by genotype, with SVR 92.0% in genotype 1, 89.3% in genotype 2 and 77.1% in genotype 3. Previous studies had reported that HCV genotype 1 and 2 patients achieved higher SVR, with lower response in genotype 3, with our result in line with these findings. The major factor influencing DAA outcomes was unrelated to HCC—the DAA regimen received.…”
Section: Discussionmentioning
confidence: 99%
“…We reopened the question of the addition of RBV to the SOF and DCV combination in 2015, when the last patient with liver cirrhosis was referred to antiviral treatment. We decided not to add RBV again, the decision being based on the preliminary data from the two real-life cohorts:32,33 the real-life data demonstrated a higher efficacy of SOF and DCV combination (93.8% SVR rate) also in genotype 3-infected cirrhotic patients in comparison with the ALLY-3 study and the SVR rate in arms with RBV was not significantly better. Nowadays, the EASL 2016 Guidelines2 recommend 12 weeks of SOF and DCV plus RBV or 24 weeks of SOF and DCV as optimal treatment regimen for hemodialyzed patients infected with HCV genotype 3, reflecting the fact that the genotype 3-infected patients with cirrhosis are considered as difficult to treat.…”
Section: Discussionmentioning
confidence: 99%